PENGARUH KOMPETENSI, LINGKUNGAN KERJA TERHADAP MOTIVASI DAN KINERJA PEGAWAI SEKOLAH TINGGI PENYULUHAN PERTANIAN (STPP) GOWA DI GOWA PROVINSI SULAWESI SELATAN - Slaviaty, Nenny; Mappatompo, Andi; Rahim, Abd Rahman (COMPETITIVENESS, 2018)
ABSTRACK                 This study aims to determine and analyze the influence of competence, work environment on motivation and performance of employees of the Gowa Agricultural Extension College (STPP) in Gowa, South Sulawesi Province as well as to identify and analyze variables that have direct and indirect influence on employee performance.                This research was conducted at the College of Agricultural Extension (STPP) Gowadi Gowa, South Sulawesi Province with a sample of 98 people. The method of analysis used in this research is quantitative method, through path analysis testing.                The results show that competence has a significant effect on motivation; The work environment has a significant positive effect on motivation; Competence has a significant positive effect on employee performance; The work environment has a positive and insignificant effect on performance; Motivation has a significant effect on performance; Competence has a significant influence on employee performance through motivation, this shows that the more appropriate the competence of employees with their work will increase work motivation and ultimately have an impact on employee performance that is getting better; The work environment has a significant influence on employee performance through motivation, this shows that the conditions of the work environment can increase employee motivation so that it has an impact on improving employee performance. Keywords: Competence, work environment, motivation and performance